The JOBS Act and Information Uncertainty in IPO Firms - Barth, Mary E.; Landsman, Wayne R.; Taylor, Daniel J. (The Accounting Review, 2017)
ABSTRACT This study examines the effect of the Jumpstart Our Business Startups Act (JOBS Act) on information uncertainty in IPO firms. The JOBS Act creates a new category of issuer, the Emerging Growth Company (EGC), and exempts EGCs from several disclosures required for non-EGCs. Our findings are consistent with proprietary cost concerns motivating EGCs to eliminate some of the previously mandatory disclosures, which increases information uncertainty in the IPO market, attracts investors who rely more on private information, and leads EGCs to provide additional post-IPO disclosures to mitigate the increased information uncertainty. Our results also are consistent with agency explanations, whereby EGCs exploit the JOBS Act provisions to avoid compensation-related disclosures, which results in larger IPO underpricing for such firms. Overall, we provide evidence on how reduced mandatory disclosure affects the IPO market.